Design of wideband microstrip antenna array at L‐band for synthetic aperture radar applications. Issue 4 (27th February 2013) - Sharma, Devendra Kumar; Pandey, Balendu Kumar; Kulshrestha, Sanjeev; Chakrabarty, S. B.; Jyoti, Rajeev
Abstract This paper presents the design and development of wideband dual‐polarized microstrip array antenna at L‐band for spaceborne synthetic aperture radar (SAR) applications. A new type of electromagnetically coupled microstrip patch fed by strip‐loaded coaxial probe has been used as single antenna element. These radiating elements have been combined to form a 2×6 array antenna using feeder network in stripline configuration. The simulated and measured performance on return loss and radiation parameters has been presented. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:903–908, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27453